2016
DOI: 10.1002/pc.24074
|View full text |Cite
|
Sign up to set email alerts
|

Potential of pine needles for PLA‐based composites

Abstract: The article describes the mechanical properties of biodegradable composites. The composites were made using biodegradable plastics like polylactic acid reinforced with Pinus roxburghii needles. The composites were characterized by their tensile strength, flexural strength, Rockwell hardness, thermal stability, and FTIR analysis as well as morphological and water absorption behavior. The composites possessed high tensile and flexural strength on addition of 8.77% fibers. The tensile and flexural strength increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
1
4
0
2
Order By: Relevance
“…The second issue with PLA is its relatively high cost. Therefore, low-cost natural fibers such as plant and animal fibers have been used to modify PLA to fabricate cost-efficient composite materials with improved toughness [ 6 , 7 ]. Among them, cellulose is one of the most abundant renewable natural polymers with enormous advantages, such as low density, worldwide availability, biodegradability, non-toxicity, and good mechanical properties [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second issue with PLA is its relatively high cost. Therefore, low-cost natural fibers such as plant and animal fibers have been used to modify PLA to fabricate cost-efficient composite materials with improved toughness [ 6 , 7 ]. Among them, cellulose is one of the most abundant renewable natural polymers with enormous advantages, such as low density, worldwide availability, biodegradability, non-toxicity, and good mechanical properties [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maleic anhydride is another coupling reagent used to increase the interfacial adhesion of biocomposites [100]. Partial removal of lignin on the henequen fibres increases the adsorption of the silane couplings and interaction among the fibre and the matrix [101]. The mechanical properties including tensile, flexural, impact strengths and tensile modulus of the biocomposites were improved several times on Jute fibre polypropylene composites using m-isopropenyl-α-α-dimethylbenzyl-isocyanate (m-TMI) as the coupling agent using grafting process.…”
Section: Chemical Modification Of Fibresmentioning
confidence: 99%
“…27 Nevertheless, the hydrophobicity, brittleness and slow degradation rate of PLA limit its clinical application in the urinary system. 28–30 At the same time, it has been reported that PCL was flexible, high elongation at break and similar processing temperature to PLA. 31 In addition, the polyether structure of mPEG enabled itself to couple a large number of water molecules and reduce its friction coefficient, thereby reducing the adhesion of encrustation on the surface of the ureter stents.…”
Section: Introductionmentioning
confidence: 97%